Corrosion Behavior of Al0.1CoCrFeNi High Entropy Alloy in Various Chloride-Containing Solutions - Wang, K.; Lan, A. D.; Qiao, J. W. (Frontiers in Materials, 2021)
The present work investigates the corrosion behavior of Al0.1CoCrFeNi high entropy alloy (HEA) in various concentrations of chloride-containing solutions. Electrochemical tests exhibit overall excellent corrosion resistance of this alloy against the attack of Cl−-containing solutions. The main type of corrosion topography presents an intergranular feature. In addition, electrochemical impedance spectroscopy (EIS) investigation of the HEA samples under immersion test suggests chloride anion–containing environment leads to the decline of passivation film quality. Further analysis of XPS results reveals that significant amounts of elements exist with atomic states in the passive films.